Educação sexual: fatores que implicam a implantação dos referenciais curriculares na prática pedagógica - SÁ, Maria Raimunda Ferreira de (2019)
It stands out as the theme “Sexual Education: Factors that imply the implantation of curricular references in pedagogical practice”, for understanding the necessity of the study in the school, because the same is little approached. It is a bibliographical research that searches through certain contexts with different authors and documents such as PCNs, to show the importance of relevance and clarification about Sexual Education as a transversal theme in the school. It had as general objective: To reflect the factors that impede the implementation of curriculum references as sexual orientation in the curricular matrix of the schools from the bibliography studied. And specific objectives: To describe the determinants for the absence of the discussion and the pedagogical work of the thematic sexual orientation by the schools; To present a context in this research, that can be adopted in the pedagogical practices according to the position of the authors studied; and; Understand from the bibliographic studies, why the cross-sectional sexual orientation theme does not appear in the curriculum planning of schools. The methodology is based on the contextualization of the bibliographical reference in books, scientific journals, articles, websites, among others, seeking the documentary contributions, a reference that allows a new way of looking at sex education in the teaching and learning process. From the readings, it is verified the need of the teachers to look for formations, to know the subject, the legislations, the public policies to guide and to implement projects that can clarify the students with the question. Thus, it is concluded that, Sexual Education manifests itself in the human being normally and has reflexes in the school, which constitutes inseparable element of the process of knowledge construction. Therefore, the quality of the pedagogical interaction must be sought with great primacy, since it will give a significant meaning to the object of knowledge, from the lived experiences or failure of the teaching-learning process, since the external reflexes considerably influence this relationship which sometimes overlaps with teaching.